Pure strontium-87 isotope in rubidium biotite from the ukrainian shield - Andreev, A.V.; Valter, A.A.; Dikiy, N.P.; Dovbnya, A.N.; Eremenko, G.K.; Lyashko, Yu.V.; Pisansky, A.I.; Storizhko, V.E.; Uvarov, V.L. (Вопросы атомной науки и техники, 2011)
In lithium pegmatites of Shpoljano-Tashlyksky ore area (Kirovograd block of the Ukrainian shield) the biotites enriched with rubidium are distinguished. X-ray and electron-microprobe study of these minerals has shown that they attributed to low ferruginous biotites of structural modification 1M. By nuclear-physics methods the concentration of rubidium, ⁸⁷Rb and ⁸⁷Sr were defined. By X-ray-fluorescent method Sr/Rb-ratio was defined. From these data the cleanliness ⁸⁷Sr s%=⁸⁷Sr/Srtot×100=96⁺⁴₋₆% received. The natural isotopic abundance of ⁸⁷Sr is 7%. Rb/Sr age of the mineral is estimated as 2.14 billion years that will be coordinated with earlier results. У літієвих пегматитах Шполяно-Ташлицького рудного району (Кіровоградський блок Українського щита) зустрінуті біотити, збагачені на рубідій. Рентгенографічне і електронно-мікрозондове вивчення цих мінералів доводить, що вони відносяться до низькозалізистих біотитів структурної модифікації 1M. Ядерно-фізичними методами визначені концентрації ⁸⁷Rb і ⁸⁷Sr, рентген-флюоресцентним методом - Sr/Rb - співвідношення. За цими даними отримали чистоту ⁸⁷Sr s%=⁸⁷Sr/Srtot×100=96⁺⁴₋₆% порівняно із звичайною розповсюдженістю ⁸⁷Sr 7%. Rb/Sr вік мінерала оцінений в 2.14 мільярди років, що узгоджується з результатами, що були отримані раніше. В литиевых пегматитах Шполяно-Ташлыкского рудного района (Кировоградский блок Украинского щита) встречены биотиты, обогащённые рубидием. Рентгенографическое и электронно-микрозондовое изучение этих минералов показало, что они относятся к низко железистым биотитам структурной модификации 1M. Ядерно-физическими методами определены концентрации ⁸⁷Rb и ⁸⁷Sr, рентген-флюоресцентным методом - Sr/Rb - отношение. Из этих данных получили чистоту ⁸⁷Sr s%=⁸⁷Sr/Srtot×100=96⁺⁴₋₆% по сравнению с обычной распространённостью ⁸⁷Sr 7%. Rb/Sr возраст минерала оценен в 2.14 миллиарда лет, что согласуется с ранее полученными результатами.